Avaliação histológica, histoquímica, morfométrica e radiográfica de traquéias de cães portadores de colapso traqueal - Paulo Eduardo Ferian (2009)
The purpose of the study reported here were to analyzed the morphological changes in trachea of dogs with tracheal collapse and the macroscopic result in this organ as well as the implications on the radiographic exams. It was selected thirty one tracheas by post-mortem assessment who presented anatomic abnormality compatible with the disease and five control tracheas group. One cervical tracheal ring and one thoracic tracheal ring were collected. The sample of two groups were processed and stained with H&E, safranina and Masson trichrome. All the animals belonging to the tracheal collapse group, presented degenerative alterations in the hyaline cartilage of tracheal rings such as replacement for fibrous connective tissue (65%) , hypocellularity (65%), decrease of the concentration of GAGs (61%), necrosis of chondrocytes with cartilage matrix calcification (55%), and the formation of cartilage isles aparted from the ring (31%). The differences were not significant in injuries between cervical and thoracic rings. It was also made a morphometric study of the macroscopic changes in the tracheal collapse. The assessment shows that occurs a dorsoventral flattening of the tracheal rings in the sick dogs and these changes were more intense in the cervicothoracic portion. In the spite of the abnormality, there is no important decrease in the static airway. The tracheal collapse is dynamic and because of this, the radiographic interpretations were important. At last, was made in the 102 dogs who have tendency to present the tracheal collapse, a radiographic evaluation in lateral views during the inspiratory and expiratory phases. It was observed a occurrence above 70% in the breeds of Poodle, Yorkshire Terrier and Maltês. The carry out of this two radiographic views, contributed for increase the diagnostic. Until now, everybody believes that the tracheal collapse occur with most frequency in the inspiratory phase on the cervical and cervicothoracic segment. This study showed that this statement isnt true